Terminal sliding mode control for active engine mounting system - Wijaya, Andika Aji; Ridhuan Siradj , Fadly Jashi Darsivan; Solihin, Mahmud Iwan; Wahyudi, Martono; Akmeliawati, Rini (2009)
This paper discusses terminal sliding mode control for active engine mounting (AEM) system to isolate vehicle engine body vibration. The engine vibration may occur due to road irregularities, at low frequency, and also reciprocating mechanism of the piston in the engine, at high frequency about 20 – 40 Hz. Active engine mounting system is designed to deal with isolation of vibration in high level frequency. A number of controllers for AEM system have been proposed. One of them is sliding mode control. However, there is no systematic method to determine sliding surface for conventional sliding mode technique to assure the system will be asymptotically stable. The main advantage of the proposed controller compared to the conventional (linear) sliding mode control is that the sliding motion to the origin (stable condition) can be reached in finite time by introducing the nonlinear sliding surface based on the concept of terminal attractors. The result shows that terminal sliding mode control not only able to attenuate the vibration but also robust to the different type of disturbance and parametric uncertainties such as mass, stiffness, and damping coefficient.